Simon sleeps over - Butler, Dori Hillestad (Butler, Dori Hillestad. Dear Beast, 2022)
"A stuck-up cat and a good-natured dog are pen pals from a distance, until a disastrous sleepover brings them together in this playful illustrated chapter book told in letters"--